Dietary Patterns and Mediterranean Diet Score and Hazard of Recurrent Coronary Heart Disease Events and All‐Cause Mortality in the REGARDS Study - Shikany, James M. (J Am Heart Assoc, 2018)
BACKGROUND: Previously, we reported on associations between dietary patterns and incident acute coronary heart disease (CHD) in the REGARDS (Reasons for Geographic and Racial Differences in Stroke) study. Here, we investigated the associations of dietary patterns and a dietary index with recurrent CHD events and all‐cause mortality in REGARDS participants with existing CHD. METHODS AND RESULTS: We included data from 3562 participants with existing CHD in REGARDS. We used Cox proportional hazards regression to examine the hazard of first recurrence of CHD events—definite or probable MI or acute CHD death—and all‐cause mortality associated with quartiles of empirically derived dietary patterns (convenience, plant‐based, sweets, Southern, and alcohol and salads) and the Mediterranean diet score. Over a median 7.1 years (interquartile range, 4.4, 8.9 years) follow‐up, there were 581 recurrent CHD events and 1098 deaths. In multivariable‐adjusted models, the Mediterranean diet score was inversely associated with the hazard of recurrent CHD events (hazard ratio for highest score versus lowest score, 0.78; 95% confidence interval, 0.62–0.98; P(T) (rend)=0.036). The Southern dietary pattern was adversely associated with the hazard of all‐cause mortality (hazard ratio for Q4 versus Q1, 1.57; 95% confidence interval, 1.28–1.91; P (Trend)<0.001). The Mediterranean diet score was inversely associated with the hazard of all‐cause mortality (hazard ratio for highest score versus lowest score, 0.80; 95% confidence interval, 0.67–0.95; P(T) (rend)=0.014). CONCLUSIONS: The Southern dietary pattern was associated with a greater hazard of all‐cause mortality in REGARDS participants. Greater adherence to the Mediterranean diet was associated with both a lower hazard of recurrent CHD events and all‐cause mortality.